2007
DOI: 10.1038/sj.pcan.4500960
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of anterior gradient-2 is significantly associated with poor survival of prostate cancer patients

Abstract: Anterior gradient-2 (AGR2) expression was examined in a series of prostate cell lines and in an archival set of prostate tissues. The relative levels of AGR2 expression in the malignant cell lines PC-3 and PC-3M were, respectively, 5.3+/-0.1 and 3.8+/-0.2 times that detected in the benign cell line PNT-2. Immunohistochemical staining in 106 cases showed that amongst seven normal cases, one (14.3%) was unstained, five (71.4%) stained weakly positive and one (14.3%) stained moderately positive. Amongst 34 benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 33 publications
3
65
1
Order By: Relevance
“…36 In contrast, another reported that increased AGR2 expression was correlated with poorer outcome in prostate cancer. 13 Similar controversy regarding the prognostic value of AGR2 expression has been observed in breast cancer; with AGR2 upregulation associated with favorable prognosis in one study, 37 and with poor prognosis in another independent analysis. 11 Previous studies of PDAC did not identify a correlation between AGR2 expression and prognosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…36 In contrast, another reported that increased AGR2 expression was correlated with poorer outcome in prostate cancer. 13 Similar controversy regarding the prognostic value of AGR2 expression has been observed in breast cancer; with AGR2 upregulation associated with favorable prognosis in one study, 37 and with poor prognosis in another independent analysis. 11 Previous studies of PDAC did not identify a correlation between AGR2 expression and prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…9 Several studies have shown that AGR2 is overexpressed and promoted tumor progression in numerous human malignancies affecting the ovary, breast, lung, prostate, and pancreas. [10][11][12][13][14] In PDAC, Ramanchandran et al 14 reported that AGR2 expression was elevated, even in PanIN1A, the earliest precursor lesion of PDAC. In this context, AGR2 promotes cancer cell proliferation, invasion, and resistance to chemotherapy, suggesting that AGR2 promotes cancer progression; however, the mechanisms underlying AGR2 function in advanced PDAC remain unclear.…”
mentioning
confidence: 99%
“…Clinical studies have also implicated the protein in inflammatory bowel disease (Zheng et al, 2006), hormone-dependent breast cancers (Thompson and Weigel, 1998;Fletcher et al, 2003;Innes et al, 2006), and a range of non-hormone cancers (Lee et al, 2006;Zhu et al, 2007). Furthermore, AGR2 predicts poor prognosis in prostate cancers (Zhang et al, 2007). Finally, expression of genes including AGR2 and others could detect circulating tumour cells in peripheral blood of advanced cancer patients (Smirnov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue sections were stained with haematoxylin and eosin to assess tumour morphology. Serial tissue sections were stained immunohistochemically to detect C-FABP expression, as described previously (14,19). The intensity of the immunohistochemical staining was classified into unstained (-), weak (+), moderate (++) and strongly positive (+++).…”
Section: Methodsmentioning
confidence: 99%